Antileukemic effect of zerumbone-loaded nanostructured lipid carrier in WEHI-3B cell-induced murine leukemia model - Rahman, Heshu Sulaiman; Rasedee, Abdullah; Chee, Wun How; Zeenathul, Nazariah Allaudin; Chartrand, Max Stanley; Swee, Keong Yeap; Abdul, Ahmad Bustamam; Sheau, Wei Tan; Othman, Hemn Hassan; Ajdari, Zahra; Namvar, Farideh; Arulselvan, Palanisamy; et al. (Dove Medical Press, 2015)
Cancer nanotherapy is progressing rapidly with the introduction of many innovative drug delivery systems to replace conventional therapy. Although the antitumor activity of zerumbone (ZER) has been reported, there has been no information available on the effect of ZER-loaded nanostructured lipid carrier (NLC) (ZER-NLC) on murine leukemia cells. In this study, the in vitro and in vivo effects of ZER-NLC on murine leukemia induced with WEHI-3B cells were investigated. The results from 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide, Hoechst 33342, Annexin V, cell cycle, and caspase activity assays showed that the growth of leukemia cells in vitro was inhibited by ZER-NLC. In addition, outcomes of histopathology, transmission electron microscopy, and Tdt-mediated dUTP nick-end labeling analyses revealed that the number of leukemia cells in the spleen of BALB/c leukemia mice significantly decreased after 4 weeks of oral treatment with various doses of ZER-NLC. Western blotting and reverse-transcription quantitative polymerase chain reaction assays confirmed the antileukemia effects of ZER-NLC. In conclusion, ZER-NLC was shown to induce a mitochondrial-dependent apoptotic pathway in murine leukemia. Loading of ZER in NLC did not compromise the anticancer effect of the compound, suggesting ZER-NLC as a promising and effective delivery system for treatment of cancers.